The Penguin historical atlas of ancient Greece - Morkot, Robert (Penguin, 1996)
The cradle of western civilization, Ancient Greece was a land of contradictions and conflict. Intensely quarrelsome and competitive, the Greek city-states consistently proved unwilling and unable to unite. Yet, in spite of or even because of this internal discord, no ancient civilization proved so dynamic or productive. The Greeks not only colonized the Mediterranean and Black Sea areas but set standards of figurative art which endured for nearly 2500 years. Charting topics as diverse as Minoan civilization, The Persian Wars, the Athenian Golden Age and the conquests of Alexander the Great, The Penguin Historical Atlas of Ancient Greece traces the development of this creative and restless people and assesses their impact not only on the ancient world but also on our own attitudes and environment.
Keywords: Antiguidade - Grécia antiga; Griekse oudheid; Géographie ancienne - Atlas; Geschichte; Atlas; Greece - History - To 146 B.C; Grèce - Civilisation; Grèce - Histoire - Jusqu'à 146 av. J.-C; Griechenland (Altertum); Griechenland; Greece -- Historical geography; Greece -- Historical geography -- Maps; Greece -- History; Griechenland -- Altertum